Chitosan as an ionophore in a polyvinyl chloride based electrode for pH detection (IR) - Mohd Hizuan Hamzah (2014)
A heterogeneous membrane pH sensor based on chitosan, polyvinyl chloride (PVC) and a suitable plasticizer was developed. The best overall performance was shown by a membrane with composition ratio of chitosan (ionophore) : PVC (binder) : 2-nitrophenyl octyl ether (2-NPOE) (plasticizer) at 20 : 30 : 30 (w/w) respectively. The potentiometric responses were linear within pH 2 to 9, limit of detection at pH 9.5, slope 56.6 0.4 mV per decade at 25.0 1.0 oC and response time of 20.0 5.0 seconds. A life time of more than 3 months was obtained. The sensor showed good selectivity and reproducibility towards hydrogen ion in the presence of a number interfering cations. Results were in agreement with a commercial pH electrode for pH measurement in fruit juice samples. The sensor has been utilized in the flow injection analysis (FIA) of pH at standard solution. The slope of 57.1 0.2 mV per decade was linear at pH range of 2 to 7 at 25.0 1.0 oC was obtained